A Comprehensive Management of Stage IV Lung Cancer through Ayurveda – A Single Case Study - Sasanoor, Mahantagouda Shivanna; Hegde, Gajanana; V. Binorkar, Sandeep; M, Namratha; S.O, Sadashiv; M. Varma, Vishnu; M. B, Deekshitha; kumar K. M, Anil; M. D., Beena; J. Patil, Sharangouda (Journal of Neonatal Surgery, 2025)
Lung cancer is the leading cause of cancer-related deaths worldwide, with smoking prevalence among patients nearing 80%. It has the highest incidence and mortality rates in men and second highest in women. This case discusses a stage IV lung cancer patient who underwent radiation and chemotherapy, experiencing severe side effects. The patient was treated with Ayurveda, which included Mriduvirechana (Gentle Detoxification) using Gandarvahastadi Erandataila, followed by Snehapana (Internal Oleation) with Mahakalyanaka Ghrita and Triphala Ghrita. Virechana (Purgation Therapy) was performed using Trivrit Lehya, accompanied by Samsarjana Krama (Post-Purgation Diet) and Rasayana (Rejuvenative) therapy with Shivagutika. Symptoms such as dry cough, chest pain, loss of appetite, weight loss, and skin discoloration reduced by 80%, with significant improvement in the patient's quality of life (QOL). While modern medicine focuses on treating cancer, it has limited solutions for alleviating suffering in advanced stages. This underscores the importance of Ayurveda in improving QOL, especially in terminal stages. The Ayurvedic treatment approach used here Kshayaja/Kshataja Kasa focused on Mridu Shodhana (gentle detoxification) and Brihmana (nourishing therapy). These Ayurveda interventions were effective in enhancing the QOL of a stage IV cancer patient, suggesting that such palliative care approaches merit further research for their potential benefits.